Theory of planned behavior: an analysis of ChatGPT usage behavior among students at Makassar State University - rusmiati, andi; Pandang, Abdullah; Buchori, Sahril (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study aims to analyze students’ behavioral tendencies in using ChatGPT amid its emerging benefits and challenges, through the lens of the Theory of Planned Behavior. The research employed a quantitative descriptive method, involving 729 students from the Faculty of Education Sciences. Data were collected through surveys and interviews, and analyzed using SPSS. The findings, which refer to the three core variables of attitude toward the behavior (ATB), subjective norms (SN), and perceived behavioral control (PBC), show that the majority of respondents (70,6%) had a high positive attitude toward using ChatGPT for academic purposes. Most students (66,0%) reported moderate subjective norms, while perceived behavioral control was high (70,1%). These results indicate that students recognize the benefits of ChatGPT and feel confident in regulating its use. Consequently, their intention to use the tool is more strongly influenced by personal attitudes and self-regulation than by social pressure. The findings also highlight students’ ability to adapt to ChatGPT in academic contexts, although institutional guidance remains essential to ensure ethical and integrity-driven usage across the academic community.